HUBUNGAN ANTARA SELF REGULATED LEARNING DAN KONFLIK PERAN PADA MAHASISWA PENGURUS UNIT KEGIATAN MAHASISWA (UKM) UNIVERSITAS NEGERI MALANG - Liza, Nur; Farida, Ika Andrini; Priyambodo, Aji Bagus; Harsono, Yudi Tri (Flourishing Journal, 2022)
Abstract: Students are obliged to complete their studies, but this is easy because students have a lot of activities to do both academic and non-academic (extracurricular), so students who join the unit often experience role conflicts between students and academic activities. The purpose of this study was to describe self-regulated learning and the role conflict of student administrators of the student activity unit of the State University of Malang and to determine the relationship between self-regulated learning and the conflict of roles of student administrators of the Student Activity Unit of the State University of Malang. The type of this research is quantitative research with correlational research design. Data collection in this study used a combination sampling technique between cluster random sampling and incidental sampling which obtained a subject of 123 students. The instruments used in this study are the self-regulated learning scale from Eva (2018) and the role conflict scale based on the definition according to Greenhaus & Beutell. This study uses product moment correlation data analysis. From data analysis obtained correlation coefficient -0.207 with p 0.022 (p < 0.05). It is recommended that students who experience role conflict can do independent learning by planning activities, making priority scales, making fun strategies to maintain motivation. Abstrak: Mahasiswa berkewajiban untuk menyelesaikan studinya, namun tidaklah mudah karena mahasiswa memiliki banyak aktivitas yang dilakukan baik aktivitas akademik maupun non akademik (ekstrakurikuler), sehingga mahasiswa yang mengikuti unit kegiatan mahasiswa sering mengalami konflik peran antara kegiatan organisasi dan kegiatan akademik. Tujuan penelitian ini adalah untuk mengetahui gambaran self regulated learning dan konflik peran mahasiswa pengurus unit kegiatan mahasiswa Universitas Negeri Malang serta mengetahui hubungan antara self regulated learning dan konflik peran mahasiswa pengurus Unit Kegiatan Mahasiswa Universitas Negeri Malang. Adapun jenis penelitian ini adalah penelitian kuantitatif dengan desain penelitian korelasioal. Pengambilan data pada penelitian ini menggunakan teknik sampling kombinasi antara cluster random sampling dan insidental sampling yang memperoleh subjek sebesar 123 mahasiswa. Instrumen yang digunakan dalam penelitian ini adalah skala self regulated learning dari Eva (2018) dan skala konflik peran yang berdasarkan definisi menurut Greenhaus & Beutell. Penelitian ini menggunakan analisis data korelasi product moment. Dari analisis data diperoleh koefisien korelasi -0,207 dengan p 0,022 (p < 0,05). Disarankan bagi mahasiswa yang mengalami konflik peran dapat melakukan self regulated learning dengan cara membuat perencanaan aktivitas, membuat skala prioritas, membuat strategi yang menyenangkan untuk mempertahankan motivasi.